Wind tunnel study on effects of various parapets on wind load of a flat-roofed low-rise building. Issue 12 (December 2017) - Huang, Peng; Peng, Xinlai; Gu, Ming
A series of wind tunnel tests were conducted to investigate the effects of parapets of different configurations and various heights on the wind loading of a flat-roofed low-rise building. Local wind pressures, area-averaged peak pressures, and overall roof uplift force on the roof were determined. Spectral analysis was also performed to better understand the mechanism of how the presence of parapets affects the wind effects on the building. Additional attention was given to the power spectral density and non-Gaussian features of the area-averaged wind pressures. The results show that low parapets (h/H no more than 0.1) often increase suctions in the roof corner region. The presence of high parapets results in a decrease in the wind effects over the roof corners; however, it also leads to a growth of the uplift force over the entire roof. Comparisons among many different parapet configurations show that the ones with the raised and bottom-slotted corners help to efficiently alleviate the worst suction on flat roofs. In addition, the high parapet acts as a low-pass filter, filters out parts of the high-frequency energy in the approach flow, and stabilizes the wind pressure distribution on roof.